Altered STAT4 Isoform Expression in Patients with Inflammatory Bowel Disease. Issue 10 (October 2015) - Jabeen, Rukhsana; Miller, Lucy; Yao, Weiguo; Gupta, Sandeep; Steiner, Steven; Kaplan, Mark H.
Abstract : Background: Crohn's disease (CD) and ulcerative colitis (UC) are the major forms of inflammatory bowel disease, and pathogenesis involves a complex interplay among genetic, environmental, and immunological factors. We evaluated isoform expression of the IL-12-activated transcription factor STAT4 in children with CD and UC. Methods: We collected biopsy samples from both patients newly diagnosed with CD and with UC. We further collected blood samples from patients newly diagnosed with CD and with UC as well as from patients who had a flare-up after being in clinical remission, and we examined the ratios of STAT4β/STAT4α mRNA. In addition to STAT4 isoforms, we measured the expression of the cytokines TNFα, IFNγ, granulocyte macrophage–colony stimulating factor, and IL-17 using polymerase chain reaction of biopsy samples and multiplex analysis of patient serum samples. Results: Ratios of STAT4β/STAT4α were increased in specific gastrointestinal tract segments in both patients with CD and those with UC that correlate with the location and severity of inflammation. In contrast, we did not observe changes in STAT4β/STAT4α ratios in biopsy specimens from patients with eosinophilic esophagitis. We also observed increased STAT4β/STAT4α ratios in the peripheral blood mononuclear cells of patients with UC and those with CD, compared with healthy controls. Ratios were normalized after patients were treated with steroids. Conclusions: Collectively, these data indicate that STAT4 isoforms could be an important noninvasive biomarker in the diagnosis and treatment of inflammatory bowel disease and that expression of these isoforms might provide further insight into the pathogenesis of IBD. Abstract : Article first published online 14 July 2015.Supplemental Digital Content is Available in the Text.